Propofol and benzocaine anesthetics responses profiles in Nile Tilapia - Gonçalves, Bruno Bastos (2020)
Improving welfare in fish requires avoiding pain, stress and suffering. Propofol, 2,6diisopropylphenol, seems to be a good candidate as a fish anaesthetic, however, no study regarding propofol influence on Nile tilapia has yet been reported. With this aim, the efficiency of propofol and benzocaine was compared as anesthetic for fish following immersion exposure. Nile tilapia (Oreochromis niloticus) was used as model due its importance in aquaculture, been the most important fish for human consumption, where 4.5 million tonnes of fish are produced worldwide. At first, determination of effective anaesthetic concentrations to induce complete anesthesia was determined, under immersion, considering time to start decubitus stage. Then the magnitude of these anesthetics was tested, measuring its effects on time remaining in decubitus, posture recovery, ventilatory frequency (VF) and latency to feed. Benzocaine induced reduction of VF under decubitus. After the anesthetic effects, VF returned quickly to basal levels. The same pattern was observed for propofol, however with no return to basal levels after recovery. Time to start decubitus was similar in both anesthetic, but time to return was higher in propofol. The latency to feed was longer in fishes submitted to propofol. Thus, propofol is a more powerful anesthetic than benzocaine in Nile tilapia, with longer duration and deeper effect. Although the common usage of propofol is by intravenous injection, here we show that immersion is efficient as an anesthetic in fish and could be adopted as a protocol in experimentation as well aquaculture management. Analgesia in fish is an area in need of significant research as only a few studies exist and they provide some contrasting results.